The ABC's of writing winning business plans : how to prepare a business plan that others will want to read--and invest in / Garrett Sutton - Sutton, Garrett
Reveals how to write an accessible and recognition-promoting business plan for any organization, discussing how new or established companies can benefit from an effectively executed business plan.